2021
DOI: 10.3390/jcm10122641
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Non-Gaussian Models of Diffusion Weighted MRI in Hepatocellular Carcinoma: A Systematic Review

Abstract: The importance of Diffusion Weighted Imaging (DWI) in hepatocellular carcinoma (HCC) has been widely handled in the literature. Due to the mono-exponential model limitations, several studies recently investigated the role of non-Gaussian DWI models in HCC. However, their results are variable and inconsistent. Therefore, the aim of this systematic review is to summarize current knowledge on non-Gaussian DWI techniques in HCC. A systematic search of the literature, including PubMed, Google Scholar, MEDLINE, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 95 publications
(182 reference statements)
0
18
0
Order By: Relevance
“…Factors including the number, distribution, and fitting methods of b values, other physiological activities (such as gland secretion and flow), ROI settings, scanning devices and field strength, imaging acquisition methods, and motion artifacts all affect data quality[ 23 , 25 , 34 , 41 ]. Increased standardization of data acquisition and analysis is imperative to facilitate the generation of reliable IVIM-DWI biomarker measures that are broadly applicable[ 74 , 77 , 78 ]. In addition, recent studies have shown that IVIM-DWI modeling of the perfusion component is constrained by the diffusion component, and a reduced D slow measure leads to artificially higher PF and D fast measures[ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factors including the number, distribution, and fitting methods of b values, other physiological activities (such as gland secretion and flow), ROI settings, scanning devices and field strength, imaging acquisition methods, and motion artifacts all affect data quality[ 23 , 25 , 34 , 41 ]. Increased standardization of data acquisition and analysis is imperative to facilitate the generation of reliable IVIM-DWI biomarker measures that are broadly applicable[ 74 , 77 , 78 ]. In addition, recent studies have shown that IVIM-DWI modeling of the perfusion component is constrained by the diffusion component, and a reduced D slow measure leads to artificially higher PF and D fast measures[ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…( 13 ) in 2005 and applied to brain tissue, which is very sensitive to tissue microstructure. It is conducive to the early detection of lesions and can reflect the tissue microenvironment structure more accurately, so it is widely used in the diagnosis and treatment of tumors ( 14 ). The IVIM bi-exponential model is an advanced noninvasive functional imaging technology ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can quantitatively provide intralesional perfusion and diffusion information by functional calculations after multiple b-value scanning without contrast agent injection, which compensates for the shortcomings of the traditional DWI mono-exponential model. DKI and IVIM combined with histogram analysis have been applied to other parts of the body ( 14 , 16 ), but little research has been done on the lungs. Zheng et al.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the most common malignant tumor in the world and also one of the main causes of cancer-related death ( 1 ). Considering the specific pathogenic mechanism and epidemiological and pathological basis of the occurrence and development of HCC, early diagnosis of HCC is difficult ( 2 ). Previous studies ( 3 , 4 ) have indicated that the pathological grade of HCC is closely related to patients’ prognosis; specifically, the postoperative survival rate of patients with well- and moderately differentiated HCC is significantly higher than that of patients with poorly differentiated HCC, and the 5-year postoperative recurrence rate of poorly differentiated HCC is as high as 70%.…”
Section: Introductionmentioning
confidence: 99%